(untitled) - Quách, Tấn An (Can Tho, 2009)
This research was done to find out the students' preferred speaking activities, to investigate the impact of these activities on their motivation in learning to speak and speaking ability at the Center for Foreign Languages in the context of Can Tho University and to examine correlation between students' motivation in learning to speak and their speaking ability.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu